Effect of Eugenia aromatica and Archidendron jiringa on oxidative stress marker in type 1 diabetes rats - Azizzuddin, Norafida; Mohamed, Suhaila; Shukri, Radhiah (Malaysian Agricultural Research and Development Institute (MARDI), 2015)
This study was conducted to assess two herbs namely Eugenia aromatica (clove) and Archidendron jiringa on malondealdehyde (MDA) level in streptozotocininduced diabetic rats. A total of 56 male Sprague Dawley rats weighing 150 – 200 g were divided into seven groups. The experiment was carried out over 6 weeks. Blood glucose level, body weight and MDA activity were measured every 3 weeks. Both herbs were able to reduce the oxidative stress of diabetic rats. MDA level decrease significantly (p <0.05) in diabetic group compared to the control at the end of the study. Blood glucose level of both normal and diabetic rats was insignificantly affected by the studied herbs. Further study on effect of these herbs on different oxidative stress marker is needed to support the present finding.